2014
DOI: 10.1111/aas.12277
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergency team activation: performance of conventional dichotomised criteria versus national early warning score

Abstract: NEWS discriminates high risk patients in a heterogenic general ward population independently of multiple confounding factors. The conventional dichotomised activation criteria were not able to detect high risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 38 publications
6
40
0
3
Order By: Relevance
“…Our results complement those of Tirkkonen et al who showed that high NEWS values were associated with serious adverse events in hospital, but MET criteria were not (13). NEWS was also independently associated with higher mortality, whereas MET criteria were not.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results complement those of Tirkkonen et al who showed that high NEWS values were associated with serious adverse events in hospital, but MET criteria were not (13). NEWS was also independently associated with higher mortality, whereas MET criteria were not.…”
Section: Discussionsupporting
confidence: 90%
“…The RCPL recommends that NEWS values of >7 should prompt assessment by an RRT (9). NEWS demonstrates better ability than other published EWSS to discriminate patients at risk of a range of clinical outcomes (6) and has been validated outside its development site (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also notable that the authors used simple dichotomized ("all or nothing") criteria for calling the MET team. Continuous scoring systems such as the modified EWS (MEWS) may be more accurate but may be more cumbersome for ward staff [16].It is important to acknowledge that a strategy of RRT implementation will result in higher ICU admission rates and workload [17]. This needs to be taken into account when allocating hospital resources.…”
mentioning
confidence: 99%
“…It is also notable that the authors used simple dichotomized ("all or nothing") criteria for calling the MET team. Continuous scoring systems such as the modified EWS (MEWS) may be more accurate but may be more cumbersome for ward staff [16].…”
mentioning
confidence: 99%